Preparing English Education Department Students for Overseas Scholarship Application - Yuzar, Ella; Mardhiah, Ainol; Rahman, Fadhlur (LSM Catimore dan Sahabat, 2024)
In order to improve a college's reputation and presentation, it is critical to encourage more graduate students to study abroad to obtain a better education that is significantly enhanced in terms of knowledge and skills. A community service program was developed to help English Language Education students at Institut Agama Islam Negeri Lhokseumawe who are having difficulty finding scholarships. The program aims to improve their knowledge and skills in taking the TOEFL test as well as writing supporting documents such as a CV, essay, motivation/recommendation letter, and study plan. A comprehensive training program was developed, including strategies for answering TOEFL questions, scholarship document writing techniques, and scholarship application simulations. Furthermore, resource persons were chosen from professionals with experience obtaining scholarships, and teaching materials were tailored to the needs of the participants to ensure that the training was successful. Before submitting their application, it is strongly recommended that they list as many accomplishments as possible, in addition to demonstrating their proficiency with the English language.